Privacy and technology: implications and challenges - Shuriye, Abdi Omar; Khalifa, Othman Omran; Mohammed Jama, Abdi Risaq (2008)
Meaning of Privacy has been changed since the massive invasion of Information and Communication Technology (ICT) into our private life advances technology have greatly expanded our ability to acquire private and confidential information. Increasingly, technology is being developed to expand our capacities to monitor ongoing actions. Making credit card purchases, placing online orders, visiting and registering at websites, and participating in online chat groups are all activities that technology allows us to monitor. The use of new technology, and particularly the Internet, increasingly requires people to disclose personal information online for various reasons such as marketing. In addition the nature of the technology has also changed the possible implications of such disclosure which has raised concerns regarding privacy. Therefore, the use of many e-services will demand that people make fine grained judgments regarding the balance between their privacy concerns and the need to disclose personal information. In this paper, the ethics dilemma surrounding privacy issues within technology was explored. Results of a study which provides detail of the interaction between people’s willingness to disclose personal information and their privacy concerns were presented. A survey was conducted through questionnaire that measured participants’ privacy concerns and behaviors using scales developed by the authors, as well as other established privacy measures. A multiple regression analysis was carried out in order to investigate any link between privacy and emerging technologies. The independent effects of situational and dispositional aspects of privacy on disclosure found in the present study have implications how privacy preferences are embedded in the latest generation of ubiquitous, convergent network devices.